Lumboperitoneal shunts for the treatment of post-traumatic hydrocephalus - Fu-Mei Chen; Ke Wang; Liang Gao; Xu-Dong Yao (Asian Pacific Journal of Tropical Medicine, 2018)
Objective: To assess the effectiveness and safety of lumboperitoneal shunt for treatment of post-traumatic hydrocephalus (PTH). Methods: A retrospective analysis of medical records of patients with lumboperitoneal shunts admitted in Shanghai Tenth People's Hospital from January 2014 to March 2017 was done. Experience with lumboperitoneal shunt placement for PTH was reviewed. The diagnosis of PTH was based on ventricular enlargement with the Evans’ index (EI>0.3) before shunt implantation. Patients were evaluated for improvements in Glasgow Coma Scale (GCS), Glasgow Outcome Scale (GOS), and EI after shunt placement. Results: Totally, the study included 34 PTH patients with the average age of 49.32 years (range: 9-67 years). The average follow-up period was (3.9±3.5) months. Before lumboperitoneal shunt, the GOS score was (4±1), the GCS score was (8.53±3.38), and the EI score was (0.40±0.08). After shunt implantation, the GOS score was (3±1), the GCS score was (10.29±3.15), and the EI score was (0.34±0.13), respectively (P<0.05). Before lumboperitoneal shunt, 24 (70.58%) patients had a GOS score of 4 (vegetative state), and 10 (29.42%) patients had a GOS score of 3 (severe disabled). After lumboperitoneal shunt, 18 (52.94%) patients had improvement in GOS (11 patients improve from GOS 4 to GOS 3, 5 patients from GOS 3 to GOS 2 and 2 patients from GOS 3 to GOS 1), 22 (64.71%) patients achieved improvement in their GCS (14 patients GCS improvements >2 and 8 patients GCS improvement=1), 21 (61.76%) patients had EI improvement (18 patients with EI<0.3). There was no complication in this study. Conclusion: Lumboperitoneal shunt placement is safe and effective for PTH, and serious complications are not observed.